Arsitektur Rumah Balla Lompoa Galesong Suku Makassar sebagai Sumber Materi Geografi Budaya - Syamsuriadi Syamsuriadi; I Komang Astina; Singgih Susilo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: The purpose of this study was to describe the meaning of the balla lompoa symbol Galesong in the Makassar tribe while still looking at the geographic context behind the shape of the balla lompoa house. This type of research is qualitative descriptive using an ethnographic approach with a perspective of symbolic interaction. The results of this study indicate that the symbols on balla lompoa have a meaning that is guided by the philosophy of the Makassar tribe, namely sulapa appaka (square). The form of balla lompoa Galesong Makassar tribe is also motivated by the location of the Galesong region which is the coastal area of the Makassar Strait. The meaning and value of the balla lompoa is very relevant to be used as a source of material in the Culture Geography Course, Department of Geography, Faculty of Mathematics and Natural Sciences, Makassar State University.Abstrak: Tujuan dari penelitian ini untuk mendeskripsikan makna simbol balla lompoa di Galesong pada suku Makassar dengan tetap melihat konteks geografi yang melatarbelakangi bentuk rumah balla lompoa itu. Jenis penelitian ini deskriptif kualitatif  menggunakan  pendekatan  etnografi dengan perspektif interaksi simbolik. Hasil penelitian ini menunjukkan bahwa simbol pada balla lompoa memiliki makna yang berpedoman pada falsafah suku Makassar yaitu sulapa appaka (persegi empat). Bentuk balla lompoa Galesong Suku Makassar juga dilatarbelakangi oleh letak  wilayah Galesong yang merupakan wilayah pesisir pantai selat Makassar. Makna dan nilai balla lompoa tersebut sangat relevan untuk dijadikan sumber materi pada matakuliah Geografi Budaya Jurusan Geografi Fakultas MIPA Universitas Negeri Makassar.